Evidence-Based Consensus Recommendations for the Evolving Treatment of Patients with High-Risk and Advanced Cutaneous Squamous Cell Carcinoma - Guilherme Rabinowits; Michael R. Migden; Todd E. Schlesinger; Robert L. Ferris; Morganna Freeman; Valerie Guild; Shlomo Koyfman; Anna C. Pavlick; Neil Swanson; Gregory T. Wolf; Scott M. Dinehart (Elsevier, 2021)
Cutaneous squamous cell carcinoma is the second most common skin cancer in the United States. Currently, there is no standardized management approach for patients with cutaneous squamous cell carcinoma who develop metastatic or locally advanced disease and are not candidates for curative surgery or curative radiation. To address this issue, the Expert Cutaneous Squamous Cell Carcinoma Leadership program convened an expert steering committee to develop evidence-based consensus recommendations on the basis of a large, structured literature review. Consensus was achieved through modified Delphi methodology. The steering committee included five dermatologists, three medical oncologists, two head and neck surgeons, one radiation oncologist, and a patient advocacy group representative. The steering committee aligned on the following clinical topics: diagnosis and identification of patients considered not candidates for surgery; staging systems and risk stratification in cutaneous squamous cell carcinoma; the role of radiation therapy, surgery, and systemic therapy in the management of advanced disease, with a focus on immunotherapy; referral patterns; survivorship care; and inclusion of the patient's perspective. Consensus was achieved on 34 recommendations addressing 12 key clinical questions. The Expert Cutaneous Squamous Cell Carcinoma Leadership steering committee's evidence-based consensus recommendations may provide healthcare professionals with practically oriented guidance to help optimize outcomes for patients with advanced cutaneous squamous cell carcinoma.